Grounded theory : a practical guide for management, business and market researchers - Goulding, Christina (Online access with subscription: SAGE research methods (Core), 2002)
Written with a clarity of style and a practical slant throughout, Grounded Theory represents a primer for organizational, business and marketing students studying for research degrees who would like to adopt the grounded theory methodology approach for their dissertation or thesis.